Lack of an atypical PDR transporter generates an immunogenic Cryptococcus neoformans strain that drives a dysregulated and lethal immune response in murine lungs - Christopher J. Winski; Peter V. Stuckey; Armando M. Marrufo; Georgina Agyei; Robbi L. Ross; Tamanna Urmi; Sarah Chapman; Felipe H. Santiago-Tirado (mBio, 2025)
ABSTRACT Cryptococcus neoformans is an opportunistic fungal pathogen responsible for >150,000 deaths every year, with a mortality rate as high as 81%. This high medical burden is due, in part, to an incomplete understanding of its pathogenesis. In a previous study, we identified a cryptococcal atypical Adenosine triphosphate (ATP)-binding cassette (ABC) pleiotropic drug resistance (PDR) transporter, PDR6, that affected antifungal resistance and host interactions. Here, we follow up on the role of PDR6 in cryptococcal virulence. In vivo, mice infected with the pdr6Δ strain display altered symptomatology and disease progression. Specifically, we observed a significant increase in the innate immune cell populations in the pdr6Δ-infected mice when compared with their WT-infected littermates. Furthermore, quantification of pulmonary cytokines/chemokines revealed a robust increase of pro-inflammatory cytokines in mice infected with the pdr6Δ mutant strain. Despite the documented sensitivity of the pdr6Δ strain to azole antifungal drugs, the treatment of pdr6Δ-infected animals with antifungals did not affect survival; however, treatment with a corticosteroid significantly extended survival, highlighting the importance of a balanced/controlled host immune response. Results with mice that mount opposing immune responses support our hypothesis that the pdr6Δ strain induces a hyper-inflammatory immune response and that the mice succumb to immune-dependent tissue damage rather than the fungal burden. This altered immune response is driven, in part, by changes in the mutant’s surface. Taken together, this study provides insights regarding cryptococcal pathogenesis and highlights additional functions of PDR-type ABC transporters in pathogenic fungi.IMPORTANCEYeasts of the Cryptococcus genus, especially C. neoformans, can cause disease with unacceptably high mortality. This is due to delays in diagnostics, ineffective treatments, and an incomplete understanding of the interactions between this fungus and our immune system. In this study, we expand our knowledge of the biological function of the PDR6 gene, particularly its effect on modulating the host’s immune response. Normally, C. neoformans infections are characterized by an anti-inflammatory response that is unable to control the yeast. In the absence of PDR6, the response to the infection is a dysregulated pro-inflammatory response that initially controls the fungi but eventually results in the death of the host due to too much tissue damage. This is due, in part, to an altered fungal surface. Given the dual role of PDR6 in modulating antifungal sensitivity and immune responses, this work provides important insights that may lead to new or improved therapeutics.